Influence of melt processing on biodegradable nisin‐PBAT films intended for active food packaging applications. Issue 13 (11th December 2015) - Zehetmeyer, Gislene; Meira, Stela Maris Meister; Scheibel, Jóice Maria; de Oliveira, Ricardo Vinicius Bof; Brandelli, Adriano; Soares, Rosane Michele Duarte
ABSTRACT: Biodegradable poly(butylene adipate‐ co ‐terephthalate) (PBAT) films incorporated with different levels of the antimicrobial peptide nisin were developed by melt processing. Structural, morphological, thermal, mechanical, and antimicrobial properties of the films were determined. The X‐ray diffraction patterns exhibited decreasing levels of intensity at 2θ values as the concentration of nisin increased. Scanning electron microscopy showed a heterogeneous morphology when higher amounts of nisin were incorporated. The antimicrobial films tested presented no significant differences in the melting temperature (123–125°C), and the crystallization temperature ranged from 69 to 75°C. The addition of nisin caused no significant modification in tensile strength values. However, results of Young's modulus and deformation at break differed significantly among samples. Active films demonstrated inhibition against the Gram‐positive bacterium Listeria monocytogenes . These results demonstrated that PBAT/nisin films produced by melt processing present a great potential for use as active food packaging materials aiming enhanced food safety. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43212. Abstract :